Simulation of Rapid Intensification of Super Typhoon Lekima (2019). Part I: Evolution Characteristics of Asymmetric Convection Under Upper-Level Vertical Wind Shear - Huang, Qijun; Ge, Xuyang; Peng, Melinda (Frontiers in Earth Science, 2021)
The role of the upper-level vertical shear (VWS) on the rapid intensification (RI) of Super typhoon Lekima (2019) is investigated with high-resolution numerical simulation. Our simulation shows that under moderate upper-level easterly VWS, the tilting-induced convective asymmetry is transported from the initially down-shear quadrant to the up-shear quadrant and wrapped around the storm center by the cyclonic flow of the storm while moving inward. This process enhances upward motions at the up-shear flank and creates upper-level divergent flow. As such, the establishment of outflow acts against the environmental flow to reduce the VWS, allowing vertical alignment of the storm. The organized outflow plays an important role in sustaining the inner core deep convection by modulating the environmental upper-level thermal structure. Accompanying deep convective bursts (CBs), cold anomalies are generated in the tropopause layer due to the adiabatic cooling by the upward motion and radiative process associated with the cloud anvil. Physically, cold anomalies at the tropopause locally destabilize the atmosphere and enhance the convections and the secondary circulation. The CBs continue to develop episodically through this process as they wrapped around the storm center to form a symmetric eyewall. The results suggest that deep convections are capable of reduce the upper level VWS, promote the development of upper-level outflow. Lekima overcame the less favorable environment and eventually intensified to become a super typhoon.